Assessment of the Implementation of the Plastic Bag Reduction Ordinance in Quezon City (2012-2016) - Braganza, Patricza Andrhea T. (Philippine Journal of Public Administration; Vol 61 No 1&2 (2017), 2019)
The Plastic Bag Reduction Ordinance has been implemented in Quezon City since 2012 to regulate the use of plastic bags in an attempt to address plastic pollution. This study assessed the implementation of the ordinance. Customers’ use of recyclable bags was directly observed in four retail stores in the District 4 of Quezon City. A survey was also conducted among 120 residents from six barangays comprising Area 24, District 4 of the city to gather data on awareness of and compliance to the ordinance. Focus group discussions and interviews with city government officials and store managers, among other stakeholders, were also conducted to enrich quantitative data. Survey results showed high level of awareness of the ordinance, but lower level of awareness of the green fund. Results of the chi-square test of independence revealed that awareness significantly differed across barangays. It is also revealed that the ordinance affects stakeholders in different ways, and that it may have somewhat reduced the percentage of plastic waste collected from households in the city. Lastly, retail stores face administrative challenges in translating green fund into meaningful environmental programs.
Keywords: Plastic Bag Reduction Ordinance, green fund, policy implementation, Quezon City